1999
DOI: 10.1002/(sici)1521-396x(199910)175:2<705::aid-pssa705>3.3.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Morphology and Characterization of Yb : YVO4 Crystal

Abstract: An Yb : YVO 4 single crysal with good optical quality and large size has been grown by the Czochralski method. We have discussed the growth shape of Yb : YVO 4 single crystal which is composed of f100g and f101g simple forms. The data of thermal expansion and specific heat of the crystal have been measured. The thermal expansion coefficients along a-and c-axis directions are a 1 1X5 Â 10 À6 /K and a 3 8X2 Â 10 À6 /K, respectively. The specific heat is 30.4 cal/mol K at 320 K. The absorption and fluorescence sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…Despite the large number of publications about luminescence properties of vanadates [1][2][3][4][5][6][7][8][9][10][11][12], the available experimental and theoretical data are not sufficient to give a unifying explanation of the nature of the luminescence centers in these compounds. There have been attempts to explain the nature of the bands in the optical spectra of vanadates by the presence of vanadium-oxygen clusters such as [VO 4 [12] (Table 4)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the large number of publications about luminescence properties of vanadates [1][2][3][4][5][6][7][8][9][10][11][12], the available experimental and theoretical data are not sufficient to give a unifying explanation of the nature of the luminescence centers in these compounds. There have been attempts to explain the nature of the bands in the optical spectra of vanadates by the presence of vanadium-oxygen clusters such as [VO 4 [12] (Table 4)).…”
Section: Discussionmentioning
confidence: 99%
“…Complex vanadium oxide compounds have drawn the attention of researchers and developers as promising luminescent materials [1][2][3][4][5][6][7][8][9][10][11][12]. The technical applications of vanadium oxides compounds have been proved by dozens of patents [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The light absorption of laser material causes thermal gradient which may disturb the laser oscillation and directly affect the quality of laser beam and laser efficiency. 10 Moreover, the thermal gradients can also lead to material fracture if they are high enough. The mechanical properties of laser material are very important for the equipment design and practical use.…”
Section: Introductionmentioning
confidence: 99%
“…For example, YVO 4 :Eu 3+ is a steadfast luminescent material used in color television, the high--pressure mercury lamp and as a scintillator in medical image detectors for more than 20 years [1]. Nd: YVO 4 crystal rather than Nd:YAG has been commercialized as laser device for its excellent monochromaticity and stability [2]. Forbes et al [3] reported the synthesis, solubility and growth of large YVO 4 and Nd:YVO 4 transparent single crystals in aqueous NaOH under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%